(untitled) (Al-Academy, 2025)
Contemporary Iraqi art witnessed artistic achievements that were within the cognitive systems that make up modern Iraqi painting, which was accompanied by the diversity of subjects in an attempt to spread aesthetic values that belong to the spirit of the era, the diversity of thought, and the absorption of its new approach, including also containing the environment and the heritage represented in drawing miniatures for the intermediate and the visualized in the mind. For Iraqi artists, from what they acquired during their travels to Western countries, the manifestations of nature were the most prominent in what the artist showed in his creative works, but for the diversity of women, they emerge from their physical appearance in the methods of presenting representations of the image of women in Iraqi painting. Connotations that carry within them more than one meaning, and it has become necessary to reveal The underlying contents and the idea that the artist wants to express, as the researcher seeks to reveal them in new formats and methods as a means of discourse that conveys ideas in different formulations. The goal of the research: trying to study the artistic forms of women, and their representations within artistic works. The second chapter includes two sections: the first: the references that put pressure on the image of women in Iraqi painting, and the second: stylistic intertextuality in Iraqi painting. As for the research sample, the intentional sample was adopted to serve the course of the research and its directions, and the most important results and conclusions. We find that the artist treated the realistic image of women with a group of Feelings, emotions, and contemplation turned towards the inner image that was addressed by his rejection of constancy and confirmation. The artist Mahood Ahmed borrowed vocabulary from the history of the Mesopotamian civilization and used it within his works, as in Sample No. (1), in addition to some other Iraqi artists